FORAGE YEILD AND COMPITITION INDICES OF CEREALS MIXED INTERCROPPING WITH FORAGE LEGUMES IN SULAIMANI REGION - Jafar, Ch. S.; Towfiq, Sh. I.; Rafat, J. Gh. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The present study was conducted in Sulaimani region at two different locations, Kanipanka and Qlyasan during winter season of 2019-2020 to estimate the response of forage yield and some competition indices to the effect of crop pure stands and their mixtures of barley and triticale intercropped with narbon vetch and grass pea with some different patterns. The experiment was designed according to Completely Randomized Block Design with three replications. As the average of both location the maximum green forage yield was produced by pure narbon vetch 32.610 ton ha-1, while pure barley produce maximum dry forage yield and dry matter % reached 5.506 ton ha-1 and 8.55% at booting stage respectively, but the crop mixture barley/grass pea at a rate 2:1 produce maximum green and dry forage yield 32.083 and 5.616 ton ha-1 respectively at booting stage. The crop mixture barley/vetch 1:1 gave maximum dry matter% 17.88% at the same stage. The highest value for total LER was 1.401recorded by the mixture of triticale/grass pea at elongation stage, while the highest relative crowding coefficient was 1.285 recorded by the same mixture at a rate 1:1 at the same cutting stage. Maximum competitive ratio for cereals was 3.652 recorded by barley in the mixture barley/grass pea 1:2 at elongation stage, while for legume it was 2.292 for narbon vetch in the mixture triticale/vetch 2:1 at booting stage.